Examination of the relationships between urban form and urban public services expenditure in China - Chunming Bo; Hengzhou Xu; Yong Liu (Administrative Sciences, 2017)
This econometric study contributes to the ongoing debate about the costs and benefits of urban form by employing interdisciplinary means-urban planning, econometrics and public administration-to explore the relationship between urban form and urban public services expenditure. In China, particularly, rapid urbanization is accompanied by an increase of urban public services expenditure and a difference in efficiency, which undermines the promotion of urban public service development. The Chinese government has paid great attention to urban sustainable development and promoting urban public services performance; however, until recently there has been a lack of empirical studies exploring the relationship between urban public services expenditure and urban form. Thus, the present research aims to analyze this issue by using relevant indicators based on an econometric model. The results provide a promising basis for improving urban public services expenditure efficiency. Based on the urban area interpreted by remote sensing data and geographic information system, two urban form metrics, the compactness ratio and the elongation ratio, are selected and quantified to describe urban compactness and urban sprawl accurately. Panel data analyses are performed using a cross-sectional dataset of the 30 cities for the years 2007, 2010 and 2013 to assess the likelihood of association between indicators of urban form and urban public services expenditure, while controlling for other determinants, such as educational level, income per capita, degree of industrialization, and unemployment rate. The results indicate that urban elongation is positively correlated to per capita urban public services expenditure and urban compactness is insignificantly correlated to it. Thus, it is recommended that policymakers consider the relationship between urban form and public services expenditure as part of urban planning and on-going strategies to promote public service efficiency.
Keywords: 350; public services expenditure; urban compactness; urban elongation; urban planning; China